Synergistic Antibacterial Activity of Clavulanic Acid and Amoxicillin Against β-Lactamase-Producing Strains of Haemophilus ducreyi - Girouard, Yves C. (1981)
The susceptibility of 47 strains of Haemophilus ducreyi to amoxicillin, clavulanic acid, and the combination of both drugs was determined by agar dilution susceptibility testing. A synergistic antibacterial activity of the combination was found for β-lactamase-producing strains.